2018
DOI: 10.1016/j.ijsu.2018.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width and neutrophil to lymphocyte ratio as predictors of outcomes in acute pancreatitis: A retrospective cohort study

Abstract: RDW and NLR can identify patients at increased risk of severe acute pancreatitis on presentation to the Emergency Department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Several studies in the literature draw attention to the relationship between the blood tests obtained at the first admission in patients diagnosed with acute pancreatitis in the emergency department with hospitalization duration and the need for intensive care. In the study by O'Connell et al, 185 patients were included, a statistical significance was observed between RDW and NLR and the duration of hospital stay [24]. In this study, the average length of stay in hospital was 7.65 days, the need for ICU was 8.1%, and mortality was 1.08%.…”
Section: Discussionmentioning
confidence: 46%
“…Several studies in the literature draw attention to the relationship between the blood tests obtained at the first admission in patients diagnosed with acute pancreatitis in the emergency department with hospitalization duration and the need for intensive care. In the study by O'Connell et al, 185 patients were included, a statistical significance was observed between RDW and NLR and the duration of hospital stay [24]. In this study, the average length of stay in hospital was 7.65 days, the need for ICU was 8.1%, and mortality was 1.08%.…”
Section: Discussionmentioning
confidence: 46%
“…Abaylı et al analyzed 435 patients with AP and found that NLR was greater in the group with a Ranson score ≥3 than the group with a Ranson score <3; thus, he concluded that NLR was a simple, practical, and effective marker for diagnosis of AP severity compared with current scoring systems. O'Connell et al revealed that NLR above five increased the risk of ICU admission. Another retrospective study revealed that the optimal cutoff value for NLR was 4.76 in predicting severity and 4.88 in predicting organ failure in acute pancreatitis .…”
Section: Discussionmentioning
confidence: 99%
“…Li et al showed that compared with PNI, CRP, RDW, and LMR, the NLR is the most powerful indicator of overall survival and has the highest prognostic value in AP patients [9]. O'connell et al found that the NLR greater than 5 increases the risk of admission to ICU [23]. Suppiah et al revealed that the NLR measured during the first 48 hours of hospitalization was significantly associated with the risk of developing a severe form of AP [24].…”
Section: Disease Markersmentioning
confidence: 99%